2014
DOI: 10.2135/cropsci2014.03.0213
|View full text |Cite
|
Sign up to set email alerts
|

New Loci Including Pse‐6 Conferring Resistance to Halo Bacterial Blight on Chromosome Pv04 in Common Bean

Abstract: Halo bacterial blight caused by Pseudomonas syringae pv. phaseolicola (Psp) is a serious seed‐borne disease of common bean (Phaseolus vulgaris L.). The disease can be controlled by major resistance (R) genes effective against specific races of the pathogen. Our objective was to characterize the R gene(s) conferring resistance to Psp Races 1, 5, 7, and 9 in the great northern dry bean germplasm release BelNeb‐RR‐1. A recombinant inbred population consisting of 76 F9–derived lines (RILs) from the cross BelNeb‐RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The severe hypersensitive reaction to Race 3 (conferred by Pse-3 ) co-segregated with the I gene locus on Pv02 (48.398–48.534 Mb) (Figure 2C, right graph; Table S1), which is consistent with previous observations (Teverson, 1991; Miklas et al, 2011, 2014). Linked markers show a pattern of segregation distortion in favor of the parent possessing the resistance allele similar to that observed in the RC population (described below).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The severe hypersensitive reaction to Race 3 (conferred by Pse-3 ) co-segregated with the I gene locus on Pv02 (48.398–48.534 Mb) (Figure 2C, right graph; Table S1), which is consistent with previous observations (Teverson, 1991; Miklas et al, 2011, 2014). Linked markers show a pattern of segregation distortion in favor of the parent possessing the resistance allele similar to that observed in the RC population (described below).…”
Section: Resultssupporting
confidence: 90%
“…From the combined data, they proposed a gene-for-gene model involving five major-effect, race-specific plant resistance ( R ) genes and corresponding pathogen avirulence ( avr ) genes (Taylor et al, 1996b). Subsequent genetic research based on linkage mapping identified the locations of major-effect R genes ( Pse-1 to Pse-6 ) on three chromosomes of P. vulgaris (Pv02, Pv04, and Pv10), which are effective against one or more Psph races (Miklas et al, 2009, 2011, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Among reference cultivars, only MDRK carried 520 bp allele, while the others carrying\500 bp band. Recently, Miklas et al (2014) reported SB10.550 originating from the previously mapped RAPD marker B10.525 tightly linked (1.4 cM) with Pse-6 as a potential marker for resistance to halo bacterial blight.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic linkage maps in common bean provided the positioning of QTLs and identified markers tightly linked to the target loci (Blair et al 2003;Miklas et al 2014;Keller et al 2015). Reliable markers for resistance against biotic and abiotic stress factors provided successful application of MAS (marker-assisted selection) in common bean (Fourie et al 2004;Kelly and Vallejo 2004;Miklas et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…phaseolicola and six resistance genes (SAP6, BAC6, SU91, BC420, R7313 and R4864) for X. axonopodis pv. phaseoli (Carlos et al, 2009;Perry et al, 2013;Miklas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%